Tenure Choice, Portfolio Structure and Long-term Care - Optimal Risk Management in Retirement - Maurice Hofmann; Hans Fehr (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Our study analyzes the savings behavior of elderly and highlights the interplay between tenure decisions, stock market investment and long-term care risk. Housing equity serves a dual purpose as a consumption good and as an asset, consequently it is important for the optimal risk structure of the financial portfolio. In addition, recent contributions also point out its implicit insurance provision to buffer long-term care shocks. Our stylized life cycle model captures these links and indicates that in Germany long-term care risks may be an important driver for homeownership. In our preferred set-up housing equity is a rather low-risky investment that even encourages stockmarket participation among elderly homeowners.
Keywords: C61; D15; G11; H55; 330; Homeownership; Life-cycle models; Stock market participation; Long-term care insurance provision